"An unlawful and contemptible adventure": the Ducoudray-Holstein expedition and US foreign policy in the early 1820s Caribbean. Issue 1 (2nd January 2023) - Mareite, Thomas
ABSTRACT: This article explores how the involvement of US citizens in projects of political revolution across the Caribbean threatened the geostrategic and economic interests of the United States in the region. In 1822, a revolutionary expedition led by a veteran of the Napoleonic wars, Henri Louis Villaume de Ducoudray-Holstein, departed from the Atlantic seaboard to overthrow Spanish rule in Puerto Rico and to establish the so-called Republic of Boricua. The republican utopia nonetheless collapsed after Curaçao's Dutch authorities arrested the expedition's leaders. This article assesses the expedition's geopolitical ramifications, highlighting how it exacerbated tensions between the US and the Spanish Empire. It also underscores the predicament of US officials, both in Washington and across the Caribbean, who sought to defend US geostrategic goals and the Union's maritime trade, even while policing US participation to illicit activities in the Revolutionary Caribbean.